Perceptual decision-making in autism as assessed by “spot the difference” visual cognition tasks - Nazia Jassim; Adrian M. Owen; Paula Smith; John Suckling; Rebecca P. Lawson; Simon Baron-Cohen; Owen Parsons (Scientific Reports, 2022)
Abstract Discriminating between similar figures proves to be a remarkably demanding task due to the limited capacity of our visual cognitive processes. Here we examine how perceptual inference and decision-making are modulated by differences arising from neurodiversity. A large sample of autistic (n = 140) and typical (n = 147) participants completed two forced choice similarity judgement tasks online. Each task consisted of “match” (identical figures) and “mismatch” (subtle differences between figures) conditions. Signal detection theory analyses indicated a response bias by the autism group during conditions of uncertainty. More specifically, autistic participants were more likely to choose the “mismatch” option, thus leading to more hits on the “mismatch” condition, but also more false alarms on the “match” condition. These results suggest differences in response strategies during perceptual decision-making in autism.